Study of chemical oxygen demand and oil-grease reduction for spent caustic from kerosene treating unit in petroleum industry wastewater treatment plant - Nur Amirah , Mohammad Ammar (2014)
Spent caustic or used caustic soda is generated from the scrubbing process in the petroleum refinery industry. Treatment is needed for spent caustic because it typically has high chemical oxygen demand (COD) and oil-grease (OG) concentration that exceeded the limit of Department of Environment (DOE) regulations. In this study, the spent caustic were tested for its COD concentration by using a spectrophotometer and its OG concentration by using Standard 5520B, liquid-liquid, partition-gravimetric method. Then, the spent caustic was treated by using coagulation and flocculation method with aluminium sulphate as primary coagulant and activated carbon and soda ash as a coagulant aid. The optimum concentration of primary coagulant and coagulant aids was determined from Jar Test. The treated spent caustic was tested for its COD and OG concentration to determine the percentage of reduction of COD and OG concentration. It is found out that the COD concentration for untreated sent caustic is at a range of 12880-23800 mg/L and OG concentration at a range of 2285-6257mg/L. From this study, the optimum concentration of primary coagulant and coagulant aids are 200 mg/L of alum and 15 mg/L of both coagulant aids, which is activated carbon and soda ash that was able to reduce 58.15% of COD and 66.21% of OG concentration in spent caustic wastewater. The usage of coagulant aid reduced the amount of alum needed and increases the coagulation and flocculation efficiency. However, the treated spent caustic still does not meet the DOE requirement for Standard B, which are 10 mg/L for OG concentration and 100 mg/L for COD concentration. Therefore, coagulation and flocculation method alone are not effective in reducing the high COD and OG concentration in spent caustic, to meet with the DOE requirement. A pre-treatment or secondary treatment should be carried out along with coagulation and flocculation treatment method. The information obtained from this study is useful for scale up purpose in the petroleum refining industry that choose coagulation and flocculation method to treat spent caustic wastewater